Intrusion prevention fundamentals - Carter, Earl (Cisco Press fundamentals series., 2006)
An introduction to network attack mitigation with IPS Where did IPS come from? How has it evolved? How does IPS work? What components does it have? What security needs can IPS address? Does IPS work with other security products? What is the "big picture"? What are the best practices related to IPS? How is IPS deployed, and what should be considered prior to a deployment? Intrusion Prevention Fundamentals offers an introduction and in-depth overview of Intrusion Prevention Systems (IPS) technology. Using real-world scenarios and practical case studies, this book walks you through the lifecycle of an IPS project-from needs definition to deployment considerations. Implementation examples help you learn how IPS works, so you can make decisions about how and when to use the technology and understand what "flavors" of IPS are available. The book will answer questions like: Whether you are evaluating IPS technologies or want to learn how to deploy and manage IPS in your network, this book is an invaluable resource for anyone who needs to know how IPS technology works, what problems it can or cannot solve, how it is deployed, and where it fits in the larger security marketplace. Understand the types, triggers, and actions of IPS signatures Deploy, configure, and monitor IPS activities and secure IPS communications Learn the capabilities, benefits, and limitations of host IPS Examine the inner workings of host IPS agents and management infrastructures Enhance your network security posture by deploying network IPS features Evaluate the various network IPS sensor types and management options Examine real-world host and network IPS deployment scenarios This book is part of the Cisco Press® Fundamentals Series. Books in this series introduce networking professionals to new networking technologies, covering network topologies, example deployment concepts, protocols, and management techniques. Includes a FREE 45-Day Online Edition.